1996
DOI: 10.3102/00028312033002383
|View full text |Cite
|
Sign up to set email alerts
|

The Culture of Sexual Harassment in Secondary Schools

Abstract: This study investigates the frequency, severity, and consequences of sexual harassment in American secondary schools, using 1993 survey data from a nationally representative sample of 1,203 8th to 11th graders in 79 public schools. We found that 83% of girls and 60% of boys receive unwanted sexual attention in school. Except for gender, social background is unrelated to either the probability or the severity of sexual harassment. However, factors characterizing the context of harassment are strongly associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 13 publications
(12 reference statements)
3
106
0
3
Order By: Relevance
“…Huerta et al documented poor academic performance in relation to sexual of harassment 24) . Similarly, Lee and colleagues found that high school students who have been harassed report paying less attention in class, receiving lower grades on individual assignments, and achieving lower grades in classes overall 25) . It is also important to assess the negative economic impacts of these abuses on the workplace as well as on the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Huerta et al documented poor academic performance in relation to sexual of harassment 24) . Similarly, Lee and colleagues found that high school students who have been harassed report paying less attention in class, receiving lower grades on individual assignments, and achieving lower grades in classes overall 25) . It is also important to assess the negative economic impacts of these abuses on the workplace as well as on the individual.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a large-scale representative study in the United States, AAUWEF (1993) reported that 87% of girls and 71% of boys reported having been sexually harassed by another student. Another study by Lee, Croninger, Linn and Chen (1996) found that the rates of sexual harassment perpetrated by teachers were lower: 20% for girls and 8% for boys. Fineran and Bennett (1998) also found that sexual harassment in schools is widespread, and most experiences involve students harassing other students.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, studies of public school students have found very high rates of harassment occurring within school settings (Kopels & Dupper, 1999;Stratton & Backes, 1997). For example, a national representative sample of secondary school students showed that 83% of girls and 60% of boys had received unwanted sexual attention in school (Lee, Croninger, Linn, & Chen, 1996). Although the majority of these experiences involved interactions among peers, about 12% of the students had been harassed by a teacher, and about one third had been harassed by other adult school staff (Lee et al, 1996).…”
mentioning
confidence: 99%
“…Perhaps because women are more often the victims of sexual harassment and other forms of sexual victimization (O'Sullivan, Byers, & Finkelman, 1998) and because they may experience more severe harassment (e.g., in secondary schools; Lee et al, 1996), the reality of their personal experiences may sensitize women to the potential threat and seriousness of inappropriate sexual attention at work or at school. Although sexual harassment history has not always been included in studies in this area, firsthand experience of sexual harassment has been found to influence later perceptions of sexual harassment.…”
mentioning
confidence: 99%